Penerapan Diskusi Kelompok dalam Meningkatkan Keaktifan Siswa Kelas XI IPS dalam Mata Pelajaran Sosiologi di SMA Muhammadiyah 1 Unismuh Makassar - Ismail, Lukman; Juleha, Juleha; Wahyuddin, Wahyuddin; Rezki.HS, Nur Fitriani; Damayanti, Novia; Martinihani, Martinihani; Mustika, Mustika (Al-DYAS, 2023)
The purpose of this research is to increase the activity of class XI IPS students in sociology, at SMA Muhammadiyah 1 Unismuh Makassar. The research method used is classroom action research (CAR). Classroom Action Research is a research activity by examining a learning activity that is given action, which is deliberately raised in a class, which aims to solve problems or improve the quality of learning in class. The cycle used in this study consists of cycle 1 and cycle 2. Each cycle consists of four stages of activity, namely planning, action, observation/evaluation, and reflection. This research was conducted at SMA Muhammadiyah 1 Unismuh Makassar. This research was conducted for 2 months starting from February 28 to May 1 in the 2022/2023 school year, according to the 2013 curriculum at Muhammadiyah 1 High School Unismuh Makassar. The subjects in this study were 28 students of class XI IPS, consisting of 14 male students and 14 female students. Determining the subject of this study was based on the results of the researchers' initial observations and interviews with teachers in the field of Sociology SMA Muhammadiyah 1 Unismuh Makassar, while technical data analysis used descriptive qualitative and quantitative analysis techniques using achievement criteria. The results of the research from the 1st meeting of the 2nd students were only 5 (46.46%) active people, this can be seen from the results of the teacher's observations in class. The 2nd meeting of students who were active in group discussions were 8 (73.73%) students. In the first cycle of the 1st and 2nd meetings, the average 60.23% was active, and the second cycle - an average of 88.04% with an increase of 27.91% was included in the high category. It can be concluded that after applying the group discussion learning model it can increase the activity of students in class.